La paradoja (Autor: James C. Hunter. Ediciones Urano, 1999) - Ana Sofía Vargas-Hernández (Universidad Nacional, Costa Rica, 2011)
Publicación: La paradoja (Autor: James C. Hunter. Ediciones Urano, 1999)